Techniques and Equivalence of Translating Taboo Words in The Wolf of Wall Street Movie - Purnomo, Budi; Yulia Sari Dewi Kusumawati (University of Surakarta, 2025)
This study aims at analyzing the translation techniques and equivalence of taboo words in The Wolf of Wall Street movie. This analysis is crucial for understanding how taboo words can be effectively translated without losing their cultural and emotional context. The method used in this research involves descriptive qualitative analysis of 584 occurrences of taboo expressions from the movie. These occurrences are categorized based on types of taboo words and translation techniques used, such as pure borrowing, literal translation, established equivalent, and reduction. This approach allows the researchers to evaluate how each technique and type of equivalence contributes to adapting taboo words in different cultural and linguistic contexts. The results indicate that epithets, the reduction technique, and the use of dynamic equivalence are the most dominant features. Reduction was found 369 times, established equivalent 190 times, literal translation 23 times, and pure borrowing 2 times. Dynamic equivalence was predominantly applied (558 instances) compared to formal equivalence (26 instances), indicating a tendency toward translations that are more natural and culturally appropriate. This study highlights the importance of balancing fidelity to the original text with cultural adaptation in translating taboo words.